Criminal desistance in Chilean women who have been deprived of liberty - Ricardo Pérez-Luco Arenas; Violeta Chitgian-Urzúa; Decio Mettifogo-Guerrero (Revista Criminalidad)
Diverse investigations have studied the phenomenon of criminal desistance in women, evincing characteristic factors for this population. The objective of this study was to explore a predictive model of the female criminal desistance from the psychosocial factors, self-efficacy, perceived social support and stage of motivation to change. Work was done with a group of 50 women who had been sentenced to deprivation of liberty punishments in Santiago, Chile. All of them participated in semi-structured interviews and gave an answer to self-report questionnaires, creating a database of characterization of the criminal process, identifying specific factors that permitted create a female desistance index. By means of multiple linear regression the aim was to determine the predictor variables, finding two profiles with different probabilities of desistance from the crime; likewise, the stages of action and maintenance explain a 25.4% of the desistance, showing the relevance of the will and the capacity of agency in the change process of the women who have infringed the law. This permits to propose the incorporation of the motivational approach in the interventions with women who have been detained and to further deepen in the found profiles.